Packed Periodic Open Cellular Structures – an Option for the Intensification of Non-Adiabatic Catalytic Processes - Ambrosetti, Matteo; Groppi, Gianpiero; Schwieger, Wilhelm; Tronconi, Enrico; Freund, Hannsjörg (Chemical Engineering and Processing, 2020)
Conductive structured catalysts offer significant potential for the intensification of gas-solid catalytic processes owing to their enhanced heat transfer properties. A major drawback is the limited catalyst inventory. Recently, packed foams were proposed to overcome the catalyst inventory limitation. The effectiveness of this concept was proven at lab-scale for intensified reactors filled with small catalyst particles. When adopting commercial foams and industrial-scale catalyst pellets, however, poor packing efficiencies are expected, limiting the potential of this concept. Similarly to foams, Periodic Open Cellular Structures (POCS) grant high heat transfer rates thanks to substantial heat conduction in their solid matrix. Additively manufactured POCS additionally offer great design flexibility. This allows for using a wider range of pellet sizes. In this work, particle packed POCS are introduced and packing efficiencies are systematically studied. Pressure drop in packed POCS is also analyzed and a suitable correlation is proposed. The heat transfer associated with this innovative reactor solution is investigated by performing non-reactive heat transfer experiments. Based on these experiments, a predictive heat transfer model is established and successfully validated with experimental data. The enormous potential of packed POCS for process intensification is illustrated by a case study of a Sabatier pilot reactor.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Additive manufacturing; Heat transfer; Pressure drop; Process intensification; Structured catalysts